PROSES ADAPTASI PENGURUS BADAN USAHA MILIK DESA DI ERA PANDEMI COVID-19 DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA KAMBUNO DAN ARA KABUPATEN BULUKUMBA - Aryo Sosiawan; Umar Nain (Jurnal Pallangga Praja (JPP), 2022)
For the sustainability of Village Owned Enterprises(BUMDesa) in the Covid-19 Pandemic Era, the BumdesManagement carried out an adaptation process. This study aims to describe the adaptation process ofBumdesa Management in the Covid-19 Pandemic Era, in improving the welfare of the people in Kambunoand Ara Villages, Bulukumba Regency. This type of research uses a qualitative approach with case studies.Informants were selected through a purposive sampling technique, which consisted of elements from thevillage head, Bumdes management, community members as beneficiaries of Bumdes at 2 research loci. Thedata collection techniques used were observation, in-depth interviews (indept interviews), and Focus GroupDiscussions(FGD). Data analysis was carried out through three stages, starting from data reduction, datapresentation and drawing conclusions and verification. The results of the study indicate that there are 3aspects of the adaptation process carried out by the Bumdesa Management, including: (1). Social aspects, providing limited basic food assistance to the community, due to the lack of budget availability for Bumdes;(2). The economic aspect, by closing certain business units so that there is a decrease in the income of theBumdes business unit and the community during the Covid-19 Pandemic; and (3). the health aspect, providingassistance to improve community nutrition, in the form of brown rice and milk for pregnant women, such asin Kambuno Village. Meanwhile in Ara, the focus is on improving environmental hygiene through processingplastic waste. However, the adaptation process in social, economic and health aspects has not been optimalin improving community welfare due to the lack of available budget in Bumdes.